Fear of Wolves and Bears: Physiological Responses and Negative Associations in a Swedish Sample - Flykt, A.; Johansson, M.; Karlsson, J.; Lindeberg, S.; Lipp, Ottmar (Taylor & Francis Inc., 2013)
Human fear is important in wildlife management, but self-reported fear provides only partial information about fear reactions. Thus, eye movements, skin conductance, and changes in heart rate were assessed during picture viewing, visual search, and implicit evaluation tasks. Pictures of bears, wolves, moose, and hares were presented to participants who self-reported as fearful of bears (n = 8), fearful of bears and wolves (n = 15), or not fearful of bears or wolves (n = 14). The feared animal was expected to elicit strong physiological responses, be dwelled upon, and be associated with negative words. Independent of fearfulness, bear pictures elicited the strongest physiological responses, and wolf pictures showed the strongest negative associations. The bear-fearful group showed stronger physiological responses to bears. The bear- and wolf-fearful group showed more difficulty in associating bears with good words. Presence of a feared animal in the search task, resulted in prolonged response time.